METHODOLOGY FOR THE FORMATION OF THE INTEGRATION OF SPEECH AND THINKING BY TEACHING STUDENTS TO WRITE ESSAYS (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses the metЙhodology of forming the integration of speech and thinking among students by teaching them how to write an essay. The main approaches to the integration of speech and thinking in the educational process are analyzed. The experience of using essay writing tasks as a means of developing students' critical thinking and academic writing skills is considered. The effectiveness of this technique for improving the quality of specialist training is substantiated.